Surgical techniques for the articular cartilage repair: literature review and meta-analysis - Burianov, Oleksandr; Omelchenko, Taras; Levytskyi, Yevhenii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To evaluate the clinical efficacy and safety of implementing the extracellular matrix (ECM), Autologous Matrix Induced Chondrogenesis (AMIC), adipose tissue derived mesenchymal stem cell (AD-MSCs), as well as bone marrow mesenchymal stem cells (BM-MSCs) for treating the osteochondral defects of knee joint and the talocrural one. Methods. Investigating by the facilities of PubMed, Embase and the manual searches, implemented from 2018 till January, 2022. There have been included articles with the І‒ІV level of evidence, studying the osteochondral defects over 0.5 сm2, with at least one-year duration of monitoring more than 10 patients, defining the scores on VAS (Visual Analogue Scale), Tegner Activity Scale, FAOS (Foot and Ankle Outcome Score). The results were evaluated after 1–2, 3–5 and over 5 years-period of monitoring. Meta-analysis was applied by the facilities of RStudio. Results. 14 investigations with 720 patients were incorporated. ECM, AMIC, AD-MSCs and BM-MSCs represented significantly better functional outcomes in comparison with the bone marrow stimulation procedures (MSP) on the VAS, Tegner Activity Scale, and FAOS scales. Patients treated according to the AMIC+BMAC (bone marrow aspirate concentrate) method showed better functional results compared to the standard AMIC technique. The rate of unsuccessful manipulations followed by revision operations in the MSP group is significantly higher than in others after 4 or more years of monitoring. The results obtained in a long-term investigation showed no deterioration after 5 years or more. Conclusions. Modern methods of cartilage repair in comparison with the creation of microfractures and microdrilling provide better quality regeneration, better long-term results, fewer complications, and higher rates of return to activity. Future studies should be longer-lasting and include more representative populations to determine the efficacy and safety of these methods.